Functional production and reconstitution of the human equilibrative nucleoside transporter (hENT1) in Saccharomyces cerevisiae. Interaction of inhibitors of nucleoside transport with recombinant hENT1 and a glycosylation-defective derivative (hENT1/N48Q). - Vickers, M F (1999)
We have produced recombinant human equilibrative nucleoside transporter (hENT1) in the yeast Saccharomyces cerevisiae and have compared the binding of inhibitors of equilibrative nucleoside transport with the wild-type transporter and a N-glycosylation-defective mutant transporter. Equilibrium binding of 3H-labelled nitrobenzylmercaptopurine ribonucleoside ¿6-[(4-nitrobenzyl)thio]-9-beta-d-ribofuranosyl purine; NBMPR¿ to hENT1-producing yeast revealed a single class of high-affinity sites that were shown to be in membrane fractions by (1) equilibrium binding (means+/-S.D.) of [3H]NBMPR to intact yeast (Kd 1.2+/-0.2 nM; Bmax 5.0+/-0.5 pmol/mg of protein) and membranes (Kd 0.7+/-0.2 nM; Bmax 6.5+/-1 pmol/mg of protein), and (2) reconstitution of hENT1-mediated [3H]thymidine transport into proteoliposomes that was potently inhibited by NBMPR. Dilazep and dipyridamole inhibited NBMPR binding to hENT1 with IC50 values of 130+/-10 and 380+/-20 nM respectively. The role of N-linked glycosylation in the interaction of NBMPR with hENT1 was examined by the quantification of binding of [3H]NBMPR to yeast producing either wild-type hENT1 or a glycosylation-defective mutant (hENT1/N48Q) in which Asn-48 was converted into Gln. The Kd for binding of NBMPR to hENT1/N48Q was 10. 5+/-1.6 nM, indicating that the replacement of an Asn residue with Gln decreased the affinity of hENT1 for NBMPR. The decreased affinity of hENT1/N48Q for NBMPR was due to an increased rate of dissociation (koff) and a decreased rate of association (kon) of specifically bound [3H]NBMPR because the values for hENT1-producing and hENT1/N48Q-producing yeast were respectively 0.14+/-0.02 and 0. 36+/-0.05 min-1 for koff, and (1.2+/-0.1)x10(8) and (0.40+/-0. 04)x10(8) M-1.min-1 for kon. These results indicated that the conservative conversion of an Asn residue into Gln at position 48 of hENT1 and/or the loss of N-linked glycosylation capability altered the binding characteristics of the transporter for NBMPR, dilazep and dipyridamole.